The facial soft tissue simulation of orthognathic surgery using biomechanical model - Obaidellah, U.H.; Merican, Amir Feisal; Abu Osman, Noor Azuan; Yahya, N.A.; Radzi, Z. (2008)
This paper describes a surgical planning, simulation and prediction of facial soft tissue appearance with regard to the orthognathic surgery. The facial soft tissue prediction is done by means of mandibular advancement through the osteotomy planning system. Our approach is based on finite element method on 3D facial models of quadrilateral elements. These elements represent different tissue regions of facial bone and skin surface semi-automatically generated from segmented patient-specific computer tomography data. We describe the surface facial model reconstruction from individualized anatomy, surgical procedures and numerical solution for static postoperative facial appearance using linear elastic finite element analysis. The physical computational modeling for the prediction of soft tissue is described. Isotropic, homogeneous and linear elastic tissue models are elaborated. The simulated result which is achieved by the advancement of lower jaw bone through the contact analysis is presented. Discussion on evaluation of the simulated result is performed with the actual findings.